Problems of Investment Literacy and Utilization of Security Crowdfunding in Digital Age Through the Islamic Capital Market - Madhukullya, Samikshya; Mahanta, Annisha; Hazarika, Anwesha (CV. Bimbingan Belajar Assyfa, 2024)
This study investigates the critical issues of investment literacy and the utilization of security crowdfunding within the Islamic capital market in the digital age. By conducting a systematic literature review (SLR), we aim to understand how investment knowledge impacts the effectiveness of Sharia-compliant security crowdfunding platforms. The review includes studies from various regions focusing on individual investors engaged in Islamic capital markets. Our findings indicate a significant gap in investment literacy among potential investors. Many lack a basic understanding of financial principles, risk management, and the specifics of Sharia-compliant investments. This deficiency hampers the effective use of security crowdfunding platforms. Additionally, the increasing reliance on digital platforms for investment activities highlights the need for targeted educational programs and stronger regulatory frameworks. To address these challenges, we recommend developing comprehensive educational initiatives focused on Islamic finance principles. Additionally, we suggest enhancing regulatory support to foster more informed and inclusive participation in the Islamic financial ecosystem. Future research should also explore specific demographic factors affecting investment literacy and the effectiveness of different educational programs.